TANGGUNG JAWAB HUKUM PLATFORM DIGITAL ATAS PENYALAHGUNAAN AI DALAM TRANSAKSI ELEKTRONIK - Kossay, Methodius; Idris, Maulana Fahmi (MAGISTRA Law Review, 2025)
The implementation of Artificial Intelligence (AI) in electronic transactions has significantly enhanced efficiency and user convenience. However, the misuse of AI by digital platforms and third parties has introduced complex legal challenges, particularly concerning the legal responsibility of digital platforms in protecting consumers from fraud and exploitation. This study aims to analyze Indonesia's regulatory framework regarding the liability of digital platforms for AI misuse in electronic transactions and compare it with regulations in other jurisdictions. Employing a normative legal approach through legislative analysis and case studies, this research reveals that Indonesia's regulatory framework still has gaps in governing algorithmic transparency and platform accountability. A comparative analysis with the regulatory frameworks of the European Union and the United States indicates that stricter regulations can effectively mitigate AI-related risks in digital transactions. Therefore, this study recommends the establishment of more adaptive policies, mandatory algorithmic transparency, and the formation of a specialized regulatory body to ensure responsible AI implementation in electronic transactions